Classes et relations sémantiques : l’exemple du verbe regarder - Grezka, Aude (Neophilologica, 2016)
The subject of this study is to broach the problems associated with polysemy and its treatment on the example of the verb regarder. The traditional lexicographical approach to the polysemy of the verb regarder consists mainly of listing synonyms. A huge disparity emerges among the proposed synonyms. We show here the importance of semantic classes to solve the problems of polysemy and thus treat various uses of the verb regarder. A sufficiently precise description can predict the link between semantics and syntax. The use of “controlled semantics” by the facts of language reflects many correlations among configurational, combinatorial and syntactic features of the verbs and their semantic characteristics.